The Inherent Properties of DNA Four-way Junctions: Comparing the Crystal Structures of Holliday Junctions - Eichman, Brandt F. (J Mol Biol, 2002)
Holliday junctions are four-stranded DNA complexes that are formed during recombination and related DNA repair events. Much work has focused on the overall structure and properties of four-way junctions in solution, but we are just now beginning to understand these complexes at the atomic level. The crystal structures of two all-DNA Holliday junctions have been determined recently from the sequences d(CCGGGACCGG) and d(CCGGTACCGG). A detailed comparison of the two structures helps to distinguish distortions of the DNA conformation that are inherent to the cross-overs of the junctions in this crystal system from those that are consequences of the mismatched dG·dA base-pair in the d(CCGGGACCGG) structure. This analysis shows that the junction itself perturbs the sequence-dependent conformational features of the B-DNA duplexes and the associated patterns of hydration in the major and minor grooves only minimally. This supports the idea that a DNA four-way junction can be assembled at relatively low energetic cost. Both structures show a concerted rotation of the adjacent duplex arms relative to B-DNA, and this is discussed in terms of the conserved interactions between the duplexes at the junctions and further down the helical arms. The interactions distant from the strand cross-overs of the junction appear to be significant in defining its macroscopic properties, including the angle relating the stacked duplexes across the junction.